Vertical relief facilitates spatial segregation of a high density large carnivore population - Farhadinia, MS; Farhadinia, MS; Heit, DR; Montgomery, RA; Johnson, PJ; Hobeali, K; Hunter, L; Macdonald, DW (Nordic Ecological Society, 2019)
Quantifying the distribution and size of home ranges is critical for understanding animal spatial dynamics. This is particularly important for large carnivores in fragmented landscapes. Most studies that estimate home range consider only a bivariate frequency distribution represented by a two‐dimensional planimetric surface. The underlying assumption of these approaches is that the animals inhabit landscapes that are completely flat. Of course, this is rarely the case. Here we investigated the influence of vertical relief and three‐dimensional landscape features on the home range patterns of a high density carnivore. Via GPS telemetry‐tracking of a population of Persian leopards Panthera pardus saxicolor (n = 6), and globally‐available digital elevation models (DEMs), we calculated the surface area of home ranges in comparison to traditional planimetric estimates. We also investigated predation patterns of leopards across elevation gradients using GPS location data and kill site analysis. The topographic measurements exceeded planimetric estimates by up to 38% which suggests that planimetric modeling underestimates home range size, particularly when animals inhabit variable terrain. We also observed that resident leopards exhibit significant altitudinal partitioning of predation, suggesting that leopards that have overlapping home ranges may still utilize exclusive hunting territories. We discuss the ways in which planimetric approaches may be underestimating aspects of animal ranging behavior and ecology. We conclude that topography should be considered, not as an ancillary metric, but as an important aspect of home range calculation. Our approach can enhance understanding of spatial requirements, population density, intra‐guild sympatric competition and conflict management of large felids inhabiting rugged landscapes.